2015
DOI: 10.1016/j.socscimed.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Toward universal coverage in Afghanistan: A multi-stakeholder assessment of capacity investments in the community health worker system

Abstract: Global efforts to scale-up the community health workforce have accelerated as a result of the growing evidence of their effectiveness to enhance coverage and health outcomes. Reconstruction efforts in Afghanistan integrated capacity investments for community based service delivery, including the deployment of over 28,000 community health workers (CHWs) to ensure access to basic preventive and curative services. The study aimed to conduct capacity assessments of the CHW system and determine stakeholder perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 26 publications
(27 reference statements)
1
42
0
Order By: Relevance
“…79 Assessments of community health worker-based services in Afghanistan have shown that despite limited awareness of this group (only about a quarter of civilians are aware), of those who accessed the services, not only were their services generally accepted and used by community members, these workers were preferred over basic or comprehensive health centre use. 94,95 A legitimate question can be asked about the transaction costs and cost-eff ectiveness for many initiatives undertaken in Afghanistan given the estimated $58 billion received in external development and relief assistance from 2001-14, 5 and the subsequent choices made. In view of the almost complete donor dependence for the fi nancing of the health and social sectors, many of these programmatic choices were implemented with close donor coordination and oversight.…”
Section: Discussionmentioning
confidence: 99%
“…79 Assessments of community health worker-based services in Afghanistan have shown that despite limited awareness of this group (only about a quarter of civilians are aware), of those who accessed the services, not only were their services generally accepted and used by community members, these workers were preferred over basic or comprehensive health centre use. 94,95 A legitimate question can be asked about the transaction costs and cost-eff ectiveness for many initiatives undertaken in Afghanistan given the estimated $58 billion received in external development and relief assistance from 2001-14, 5 and the subsequent choices made. In view of the almost complete donor dependence for the fi nancing of the health and social sectors, many of these programmatic choices were implemented with close donor coordination and oversight.…”
Section: Discussionmentioning
confidence: 99%
“…interventions in countries such as Nepal [82,90], Ugunda [117,118] Rwanda [75], Tanzania [50,77], Ethiopia [119], Afghanistan [62] and…”
Section: Discussionmentioning
confidence: 99%
“…The last reviewed is the CHW programme in Afghanistan, which was founded in 2003 as a postwar redevelopment effort (10). This programme is run by 29 international NGOs with some governmental involvement, and being the youngest of the programmes, it has been possible to model its structure and organization on other global CHW programmes (11).…”
Section: Comparison Of Chw Programmes In Egypt Pakistan and Afghanistanmentioning
confidence: 99%
“…In Egypt and Pakistan there is an educational requirement for CHWs. Egypt relies on community members, ideally young married women with not too many children, to volunteer for the job of raedat (6,7,11). Community leaders are often relied upon to recruit promising candidates.…”
Section: Selection and Demographics Of Chwsmentioning
confidence: 99%
See 1 more Smart Citation